A Coupled Model for Solution Flow and Bioleaching Reaction Based on the Evolution of Heap Pore Structure. (2nd November 2014) - Yin, Shenghua; Chen, Xun; Ma, Chi; Wang, Leiming; Wu, Aixiang
Abstract : Based on the basic seepage law, equations have been derived to descript the solution flow within the copper ore heap which is treated as anisotropy porous media. The relationship between heap permeability and pore ratio has been revealed. Given the consideration of cover pressure and particle dissolution, pore evolution model has been set up. The pore evolution mechanism, due to the process of dissolution, precipitation, blockage, collapse, and caking, has been investigated. The comprehensive model for pore evolution and solution flow under the effect of solute transport and leaching reaction has been established. A trapezoidal heap was calculated, and the estimated results show that permeability decreases with the decreasing of pore ratio. Therefore, the permeability of the heap with small particles is relatively low because of its low pore ratio. Furthermore, permeability and height are found to be the two main factors influencing the solution flow.